Chronic dislocation of proximal interphalangeal joint with mallet finger : a case report - Hussin, Paisal; Subramaniam, Mahendran; Ng, Eng Seng (BioMed Central, 2008)
We report a case of chronic dislocation of proximal interphalangeal joint with mallet finger.